Editorial (Cadernos de Sociomuseologia, 2018)
The present issue of the Journal of Sociomuseology, brings together a set of texts that deal with contemporary themes of museology in which the connections with the construction of Sociomuseology theory are understood directly and indirectly. In all cases, the texts are based on a substantive work on the ground, based on the proposals of interpretation presented by the authors.From now on Cadernos de Sociomuseologia has the very significant support of the Chair "Education, Citizenship and Cultural Diversity" proposed by our Department of Museology and in good time approved by UNESCO.